PENGARUH INTELLECTUAL CAPITAL (IC) TERHADAP IMPLEMENTASI PEMBENTUKAN CADANGAN KERUGIAN PENURUNAN NILAI (CKPN) PSAK 71 DAN KESEHATAN PERUSAHAAN PERBANKAN - Sinta Kumala Sumertaputri; Sunitha Devi (Universitas Pendidikan Ganesha, 2023)
This study examines the impact of intellectual capital on the implementation of the formation of PSAK CKPN 71 and bank soundness level in 44 banks registered on the Indonesia Stock Exchange (BEI). Using Resource-Based Theory as a theoretical framework, the study analyzes data from the year 2020 and uses regression analysis to test the relationship between intellectual capital, the implementation of PSAK CKPN 71, and bank soundness level. The study finds that intellectual capital has a positive impact on the implementation of the formation of PSAK CKPN 71. The study also finds that intellectual capital has a positive impact on bank soundness level, as measured by the RGEC index. The study suggests that banks should continue to invest in the development of their intellectual capital to enhance soundness level and their ability to implement PSAK CKPN 71 to comply with regulatory requirements and maintain their financial stability, especially during challenging economic times. However, the study has several limitations, including a small sample size, doesn’t examine the specific components of intellectual capital, and focuses on only one country's sector. Despite these limitations, the study contributes to the literature on intellectual capital, PSAK CKPN 71, and bank soundness level, and provides practical implications for banks and policymakers in Indonesia. Keywords : Intellectual capital, CKPN PSAK 71, Bank soundness level, RGEC